(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The nine months of Artaud’s travels through Mexico, usually treated as a footnote in his biography, need to be seen as more than that: they were a turning point in the direction of his work/life. For Jay Murphy (2017), there would be an Artaud before and another after his journey to Mexico, because we can observe a profound metamorphosis in his work, even if we set his “madness” aside. A paradigm shift that encompasses the evolution of a Theatre of Cruelty towards the concept of the Body without Organs. Within this context, this text first aims to critically present, in a post-colonial perspective, Artaud’s intentions in seeking a primordial theatrical language in the Mexican canyons, its limits and possibilities, and secondly, to interrogate how racial issues were problematized in such a quest and how they reverberate through his work and beyond, radically affecting and changing the field of Theatre and Performance Studies.